"Dizziness of Freedom": Anxiety Disorders and Metaphorical Meaning-making. (2nd October 2022) - Moskaluk, Kalina; Zlatev, Jordan; van de Weijer, Joost
ABSTRACT: Would metaphors used in the context of psychotherapy by people who experience various forms of anxiety disorders differ from those used by people who experience stress? We investigated this question with the help of the Motivation & Sedimentation Model (MSM), a theory of meaning-making developed within the synthetic new discipline of cognitive semiotics. The analysis of a sample of ten transcripts of psychotherapy sessions concerning the topic of anxiety, and a comparable sample concerning stress, showed a significantly stronger proportion of conventionalized metaphors in the stress sample, and a marginally significant difference in the number of innovative metaphors in the anxiety sample. These results suggest that lived experience of an anxiety disorder or another form of maladaptive anxiety affects metaphorical meaning-making, and manifests itself in spontaneous metaphor use. Furthermore, as a result of the conceptual and the empirical investigations of the topic, we propose novel theoretical and operational definitions of the notion of metaphoricity.